HIV-1 Treatment-as-Prevention. Issue 24 (June 2015) - Tang, Zhenzhu; Lan, Guanghua; Chen, Ying Qing; Zhu, Qiuying; Yang, Xiaoyi; Shen, Zhiyong; Chen, Yi; Zhang, Heng; Kan, Wei; Xing, Hui; Ruan, Yuhua; Shao, Yiming; et al.
<x xml:space="preserve">Abstract</x> Abstract The Chinese national observational cohort study suggests that the treatment-as-prevention (TasP) approach can be an effective public health HIV-1 prevention strategy. However, results from that study may have been biased because the follow-up time of index patients prior to their initiation of antiretroviral therapy (ART) was excluded. In this study, we correct for such bias by using an extended time-dependent Cox regression model to conduct a cohort study analysis of serodiscordant couples in Guangxi of China, inclusive of all follow-up time. During the follow-up of this observational cohort study of HIV-1 sero-discordant couples, the positive index partners may have never be treated with ART, or enter untreated but subsequently began treatment, or may have been treated immediately upon entry into the public health system. The treatment effectiveness of ART in HIV-1 acquisition among HIV-negative partners is assessed by the extended Cox regression model with treatment status as a time-varying covariate. A total of 6548 sero-discordant couples were included in the cohort study analysis. Among them, 348 negative partners sero-converted. HIV seroincidence was significantly higher among the nontreated (4.3 per 100 person-years, 3.7–4.9) compared with those receiving ART (1.8 per 100 person-years, 1.5–2.0). An overall 35% reduction in risk of HIV transmission was associated with receiving ART (adjusted hazard ratio [AHR] 0.65, 95% confidence interval [CI] 0.51–0.83), and the yearly risk reduction was also significant in the first 3 consecutive years of follow-up. Moreover, ART was found to be significantly inversely associated with multiple baseline characteristics of index partners. TasP may be feasible on a national or regional scale. In addition to other proven preventive strategies such as the use of condoms, ART adherence to maintain viral suppression would then be the key challenge for successful TasP implementation.